2022
DOI: 10.3390/mi13101617
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of 144-Gbps Photonics-Assisted THz Wireless Transmission at 500 GHz Enabled by Joint DBN Equalizer

Abstract: The THz wireless transmission system based on photonics has been a promising candidate for further 6G communication, which can provide hundreds of Gbps or even Tbps data capacity. In this paper, 144-Gbps dual polarization quadrature-phase-shift-keying (DP-QPSK) signal generation and transmission over a 20-km SSMF and 3-m wireless 2 × 2 multiple-input multiple-output (MIMO) link at 500 GHz have been demonstrated. To further compensate for the linear and nonlinear distortions during the fiber–wireless transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…According to the graph, frequencies above 300 GHz are mostly handled utilizing opto-electronic techniques. The greatest transmission bit rate of 110 Gbit/s has been reached among all-electronics approaches at 240 GHz [35], while the opto-electronics approach has hit 140 Gbit/s at 500 GHz [36].…”
Section: Thz Waves: Meeting High-speed Communication Needsmentioning
confidence: 99%
“…According to the graph, frequencies above 300 GHz are mostly handled utilizing opto-electronic techniques. The greatest transmission bit rate of 110 Gbit/s has been reached among all-electronics approaches at 240 GHz [35], while the opto-electronics approach has hit 140 Gbit/s at 500 GHz [36].…”
Section: Thz Waves: Meeting High-speed Communication Needsmentioning
confidence: 99%
“…With the advances in broadband terahertz devices and the design of novel digital signal-processing routines, high-speed terahertz communications could be realized. In this Special Issue, three terahertz communicating systems were analyzed and demonstrated [ 9 , 10 , 11 ], including a 144 Gbps photonics terahertz communication system working at 500 GHz [ 9 ], a W-band communication and sensing convergence system [ 10 ], and an analysis of secure terahertz communications with perfect electric conductor (PEC) and multiple eavesdroppers [ 11 ].…”
mentioning
confidence: 99%
“…Terahertz wireless communication systems based on photonics have emerged as promising candidates for 6G communications, capable of providing hundreds of Gbps or even Tbps data capacity. Liu et al [ 9 ] experimentally demonstrated a 144 Gbps dual-polarization quadrature-phase-shift-keying (DP-QPSK) signal generation and transmission over a 20 km SSMF and 3 m wireless 2 × 2 MIMO link. A novel and low-complexity joint deep belief network (J-DBN) equalizer was proposed to compensate for linear and nonlinear distortions during fiber–wireless transmission.…”
mentioning
confidence: 99%